Bidirectional relationships between inflation and key monetary indicators in Indonesia: Exploring short- and long-run dynamics - Amalia, Nur Azizah; Zahra, Siti Fatimah; Lestari, Fitra Dila (Nur Science Institute, 2025)
This study aims to analyse the effect of money supply, rupiah exchange rate, and interest rate (BI Rate) on inflation, and vice versa, in Indonesia from 2016 to 2024, with a total of 100 observations. The method employed is a quantitative approach utilizing Vector Autoregression/Vector Error Correction Model (VAR/VECM) analysis techniques to identify both short-term and long-term effects. The results of the study indicate that the money supply and inflation do not significantly influence each other in either the short or long term. The exchange rate has a negative and significant influence on inflation in the long term. In contrast, the interest rate shows a positive and significant influence on inflation only in the long term. The results of the Impulse Response Function (IRF) and Variance Decomposition (VD) analyses confirm that the exchange rate is the most effective variable in explaining variations in inflation. In contrast, the roles of money supply and interest rates are relatively low. These findings indicate the importance of exchange rate stabilization as the primary strategy in controlling inflation in Indonesia.